Cognitive and Electrophysiological Correlates of the Bilingual Stroop Effect - Naylor, Lavelda J.; Stanley, Emily M.; Wicha, Nicole Y. (Frontiers in Psychology, 2012)
The bilingual color-word Stroop effect is commonly half the magnitude when naming and reading languages are different than the same. This between-within language Stroop difference (BWLS) is likened to a response set effect, with greater response conflict for response relevant than irrelevant words. The BWLS was analyzed in 2 experiments. Color congruent and incongruent words (Exp 1) appeared in the naming language or not (single), or randomly in both languages (mixed). The BWLS effect was observed in both balanced and unbalanced bilinguals. However, color congruent trials during mixed-language blocks led to slower times between than within languages, indicating that response irrelevant stimuli interfered with processing. To investigate the neural timing of the BWLS effect (Exp 2), event related potentials were recorded while balanced bilinguals named silently. Replicating monolingual findings, an N450 effect was observed with larger negative amplitude for color incongruent than congruent trials (350-550 ms post stimulus onset). This effect was equivalent within and between languages, indicating that color words from both languages created response conflict, contrary to a response set effect. A sustained negativity followed with larger amplitude for color incongruent than congruent trials, resolving earlier for between than within language Stroop. The effect shared timing (550-700 ms), but not morphology or distribution with a previously reported sustained potential. Finally, a larger early negativity (200-350 ms) was observed for between than within languages independent of color congruence. This no-go N2-like negativity may reflect processes of inhibitory control that facilitate the resolution of conflict at the sustained negativity, while the N450 reflects parallel processing of distracter words, independent of response set. In sum, the BWLS reflects brain activity over time with contributions from language and color conflict at different points.